Modelling and robust control of an unmanned coaxial rotor helicopter with unstructured uncertainties. (January 2017) - Dong, Zhi-Yan; Liu, Shun-An; Liu, Chao; Liu, Jin-Lin; Feng, Lei
A complete methodology for an unmanned coaxial rotor helicopter with unstructured uncertainties was proposed to achieve high-accuracy tracking performance from modelling to robust control. An integrative approach was introduced to systematically construct a whole dynamic model. The key parameters were selected carefully after iteratively being checked by empirical coefficients to decrease the budget and risk of programme. Moreover, a new control scheme is proposed to simultaneously incorporate six inputs to control six states based on the investment of singularity value responses and the general rule of relative gain array. Coprime factor uncertainty model is considered to represent a class of unstructured uncertainties, such as unmolded actuator dynamics and unpredicted interferences between two rotors. Furthermore, theH ∞ loop-shaping control was proposed to apply the control design of the coaxial rotor helicopter to manage complicated uncertainties and multivariable coupling. Finally, simulation results show the effectiveness of the proposed controller design in the step response of the closed loop. The stable closed-loop plant is achieved and the tolerant size of unstructured uncertainty is up to 36.09%. Good step responses and satisfied decoupling were also investigated in detail.